Publishing for library science students a handbook - Arlante, Salvacion Manuel (Salvacion Manuel-Arlante and LS 221 class '91-'92 (Second Semester), U.P. Institute of Library Science, 1992)
The aim of this book is to teach Library Science students the essential elements of publishing, the process of book production and book design. This book contains fundamentals of publishing as well as its relationships to printers, book sellers, rights, libraries, and book production. A glossary is included in the book.